Cryo-EM structure of the tetracycline resistance protein TetM in complex with a translating ribosome at 3.9-Å resolution - Arenz, Stefan (Proc Natl Acad Sci U S A, 2015)
Ribosome protection proteins (RPPs) confer resistance to tetracycline by binding to the ribosome and chasing the drug from its binding site. Current models for RPP action are derived from 7.2- to 16-Å resolution structures of RPPs bound to vacant or nontranslating ribosomes. Here we present a cryo-electron microscopy reconstruction of the RPP TetM in complex with a translating ribosome at 3.9-Å resolution. The structure reveals the contacts of TetM with the ribosome, including interaction between the conserved and functionally critical C-terminal extension of TetM with a unique splayed conformation of nucleotides A1492 and A1493 at the decoding center of the small subunit. The resolution enables us to unambiguously model the side chains of the amino acid residues comprising loop III in domain IV of TetM, revealing that the tyrosine residues Y506 and Y507 are not responsible for drug-release as suggested previously but rather for intrafactor contacts that appear to stabilize the conformation of loop III. Instead, Pro509 at the tip of loop III is located directly within the tetracycline binding site where it interacts with nucleotide C1054 of the 16S rRNA, such that RPP action uses Pro509, rather than Y506/Y507, to directly dislodge and release tetracycline from the ribosome.